2011
DOI: 10.1007/s00726-011-1121-x
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation reduces oxidative stress biomarkers after acute exercise in rats

Abstract: The objective of this study was to evaluate the effect of creatine supplementation on muscle and plasma markers of oxidative stress after acute aerobic exercise. A total of 64 Wistar rats were divided into two groups: control group (n = 32) and creatine-supplemented group (n = 32). Creatine supplementation consisted of the addition of 2% creatine monohydrate to the diet. After 28 days, the rats performed an acute moderate aerobic exercise bout (1-h swimming with 4% of total body weight load). The animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…In this work, the adenine – treated rats exhibited the urinary and plasma profile of several traditional and novel markers of renal damage, as reported by us and others [20], [36], [37]. Most of these were improved in rats given either GA or SE, and even more so in rats given GA and subjected to SE at the same time, supporting our hypothesis that the ameliorative action of GA on adenine- induced CRF is further enhanced by SE.…”
Section: Discussionsupporting
confidence: 89%
“…In this work, the adenine – treated rats exhibited the urinary and plasma profile of several traditional and novel markers of renal damage, as reported by us and others [20], [36], [37]. Most of these were improved in rats given either GA or SE, and even more so in rats given GA and subjected to SE at the same time, supporting our hypothesis that the ameliorative action of GA on adenine- induced CRF is further enhanced by SE.…”
Section: Discussionsupporting
confidence: 89%
“…CMH supplementation with a dose of 1200 mg/kg significantly decreased the contents of lactate and GP in pectoralis major muscle, indicating that the reduction muscle glycolysis by CMH supplementation is probably the reason for maintain meat quality of transported broilers. In addition, it has been demonstrated that creatine can attenuate acute stress responses via direct antioxidant activity (Lawler et al, 2002;Deminice and Jordao, 2012). We thus recommended that further studies are needed to investigate whether the protective effect of CMH supplementation for maintaining meat quality in transported broilers is also closely related to its antioxidant activity.…”
Section: Creatine Monohydrate In Transported Broilersmentioning
confidence: 99%
“…They found that CMH can not only increase growth of pigs (James et al, 2002), but also help to improve the quality of chicken meat (Young et al, 2004). In addition, some studies also reported a new function of creatine to attenuate acute stress responses by effectively quenching superoxide anions and other aqueous radicals (Lawler et al, 2002;Deminice and Jordao, 2012). However, there is limited information concerning the effects of CHM on muscle energy metabolism and meat quality of broiler chickens when experiencing transport stress.…”
Section: Introductionmentioning
confidence: 99%
“…According to Deminice and Jordao (2012), Cr supplementation can decrease oxidative stress markers in plasma and muscle after a moderate aerobic exercise like swimming. Creatinesupplemented rats demonstrate antioxidant and protective effects, decreasing reactive oxygen species (ROS) when compared with rats without supplementation.…”
Section: Introductionmentioning
confidence: 99%